Diagnostic Accuracy of Ultrasonography in Detection of Hepatocellular Carcinoma in Patients with Chronic Liver Disease Taking CT as Gold Standard - Khan, Siddiqa Ahmed; Nayyar, Shaista; Qureshi, Faryal; Gohar, Syed Fawad; Mumtaz, Memoona (Indus Journal of Bioscience Research, 2025)
Objective: To determine the diagnostic accuracy of ultrasound in detecting hepatocellular carcinoma (HCC) among patients with chronic liver disease (CLD), using contrast-enhanced computed tomography (CECT) as the gold standard. Methods: This cross-sectional diagnostic accuracy study was conducted at the Department of Radiology, PAF Hospital Islamabad. A total of 129 patients with CLD and focal hepatic lesions on ultrasound were included. Ultrasound findings were compared with CECT findings. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated. Stratified analysis was performed for potential confounders. Results: The mean age was 53.40 ± 14.15 years. On CECT, 64 (49.6%) lesions were malignant. Ultrasound demonstrated sensitivity of 82.8%, specificity of 92.3%, PPV of 91.4%, NPV of 84.5%, and overall diagnostic accuracy of 87.6%. Stratified analysis showed consistently high diagnostic performance across age, gender, duration of CLD, etiology, Child-Pugh class, and lesion number. Conclusion: Ultrasound demonstrates high diagnostic accuracy in detecting HCC in CLD patients and remains a reliable, cost-effective first-line imaging modality in resource-limited settings.